2004
DOI: 10.1073/pnas.0306141101
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in extracellular calcium concentration directly control osteoblast function in the absence of calciotropic hormones

Abstract: We investigated the direct effects of changes in free ionized extracellular calcium concentrations ([Ca 2؉ ]o) on osteoblast function and the involvement of the calcium-sensing receptor (CaR) in mediating these responses. CaR mRNA and protein were detected in osteoblast models, freshly isolated fetal rat calvarial cells and murine clonal osteoblastic 2T3 cells, and in freshly frozen, undecalcified preparations of human mandible and rat femur. In fetal rat calvarial cells, elevating [Ca 2؉ ]o and treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
262
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(281 citation statements)
references
References 46 publications
9
262
0
3
Order By: Relevance
“…We next demonstrated that macrophages are essential for osteoblast mineralization in response to the physiological proanabolic stimulus of elevated extracellular calcium (28). We demonstrated that both OsteoMacs and BMM were able to promote osteoblast mineralization in response to this stimulus.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We next demonstrated that macrophages are essential for osteoblast mineralization in response to the physiological proanabolic stimulus of elevated extracellular calcium (28). We demonstrated that both OsteoMacs and BMM were able to promote osteoblast mineralization in response to this stimulus.…”
Section: Discussionmentioning
confidence: 77%
“…Extracellular calcium is known to be an important physiological stimulus of bone formation (28) and high extracellular calcium concentrations are a characteristic feature of the bone microenvironment (29). The apparent macrophage contribution to osteoblast mineralization in vitro (Fig.…”
Section: Macrophages Are Required For Osteoblast Mineralization In Rementioning
confidence: 99%
“…This is difficult to understand because the effect of even large variations in calcium intake levels on extracellular calcium concentrations [Ca 2 þ ] o is attenuated (Dvorak et al, 2004;Brown and Lian, 2008;Chang et al, 2008), as well as in limitation of cellular growth of normal and neoplastic cells (Rodland, 2004). Conversely, low dietary calcium causes hyperparathyroidism by impairment of CaR activity and, by the same token, can be linked to the development of osteoporosis and of various malignancies.…”
Section: Role Of the Extracellular Car In Control Of Cellular Functionsmentioning
confidence: 99%
“…In addition, because of the dissociation of calcium hydroxide in the culture medium, differences in calcium and hydroxyl concentrations between groups should also take place. Whereas slightly higher extracellular calcium concentration than physiological values has been shown to stimulate osteoblast cell viability, proliferation, differentiation, and function (16), cellular calcium overload can cause cytotoxicity and trigger either apoptotic or necrotic cell death (17). Concerning the hydroxyl ion concentration, its higher levels have been directly correlated with altered extracellular matrix organization, reduced ALP activity, and bone-like nodule formation in osteogenic cell cultures (18).…”
Section: Discussionmentioning
confidence: 99%